Línea de la sonrisa y medidas morfométricas labiales, de un grupo de individuos de población Colombiana (2023)
The smile line is an expression related to facial aesthetics. This is an imaginary curve that forms in the mouth when a person smiles and follows the curvature of the lower lip. Its position is essential to achieve natural aesthetic results appropriate to the anatomical characteristics of the patients